Trajectories of systemic agent use and associated depression- and anxiety-related health care costs among patients with psoriasisCapsule Summary - Raymond Milan, BSc, MSc; Jacques LeLorier, MD, PhD; Eric A. Latimer, PhD; Marie-Josée Brouillette, MD; Anne Holbrook, MD, PharmD, MSc; Ivan V. Litvinov, MD, PhD; Elham Rahme, PhD (Elsevier, 2022)
Background: Systemic treatment patterns and related mental health disorders and economic burden among patients with psoriasis are largely unknown. Objective: To assess systemic treatment patterns and associated depression and anxiety-related health care costs among patients with psoriasis initiating a conventional systemic treatment (CST). Methods: Using a retrospective cohort design with sequence and cluster analyses, we assessed systemic treatment trajectories (CST and tumor necrosis factor inhibitors or ustekinumab, [TNFi/UST]) over a 2-year period following CST initiation. We compared health care costs between trajectories using 2-part models. Results: We included 781 patients and identified 8 trajectories: persistent methotrexate users, persistent acitretin users, early CST discontinuation, late methotrexate discontinuation, switch to TNFi/UST, adding TNFi/UST, discontinuation then restart on methotrexate, and discontinuation then restart on acitretin or multiple CST switches. Overall, 165 (21%) patients incurred depression- and anxiety-related health care costs (median annual cost, CAN$56; quartiles, $14-$127). Compared with persistent methotrexate users, adding a TNFi/UST (cost ratio, 3.63; 95% CI, 1.47-5.97) and discontinuation then restart on acitretin or multiple switches between systemic agents (cost ratio, 13.3; 95% CI 5.76-22.47) had higher costs. Limitations: Trajectory misclassification may have occured. These date represent an association, and causality cannot be inferred, particularly given the risk of confounding. Conclusion: Depression- and anxiety-related health care costs were high among patients adding TNFi/UST and those discontinuing then restarting on acitretin or experiencing multiple switches between systemic agents.